Comparative Efficacy of Face-to-Face and Right-Rear Upright Intubation in a Randomized Crossover Manikin Study - Cheng-Wei Tseng; Chung-Shiung Wen; Sheng-Han Yu; Yung-Cheng Su; Shu-Sheng Li; Hsin-Ling Chen; Tzu-Yao Hung (Western Journal of Emergency Medicine)
Introduction: Upright intubation is essential for managing difficult airways but can be challenging, especially for less experienced clinicians. Face-to-face intubation may lower first-pass success rates due to unfamiliar orientation. New videolaryngoscope devices have the potential to improve intubation success. We aimed to compare first-pass success rates, intubation duration, and glottic view between the right-rear and face-to-face approaches, using channeled videolaryngoscope, hyperangulated videolaryngoscope, and video stylet for upright intubation. Methods: We conducted a cross-over manikin simulation study involving 30 participants—19 attending physicians, six residents, and five nurse practitioners—to compare the efficacy of these devices to a standard Macintosh videolaryngoscope, using both right-rear and face-to-face approaches. Results: We used Cox regression analysis to calculate hazard ratios for the following variables: first-pass success rate; intubation time; glottic view quality (Cormack-Lehane grade [C-L]); and percentage of glottis opening score (POGO]. The right-rear approach demonstrated a substantial improvement in first-pass success rates compared to face-to-face, with rates of 93% vs 78% and a hazard ratio of 2.10 (95% confidence interval 1.58–2.80). Additionally, both the video stylet and channeled videolaryngoscope techniques further optimized first-pass success rates and enhanced glottic visualization, achieving a CL grade I view and POGO scores of 100%, even in the inverted face-to-face orientation. These devices outperformed the standard Macintosh and hyperangulated videolaryngoscopes. Conclusion: The right-rear approach was associated with higher first-pass success rates and provided a more familiar orientation for operators during upright intubation. Video stylets and channeled videolaryngoscopes also contributed to improved success rates, shorter intubation times, and better glottic visualization.